2016
DOI: 10.1038/srep27758
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-induced reversible switch of the neuron-specific enolase promoter from Purkinje neurons to Bergmann glia

Abstract: Neuron-specific enolase (NSE) is a glycolytic isoenzyme found in mature neurons and cells of neuronal origin. Injecting adeno-associated virus serotype 9 (AAV9) vectors carrying the NSE promoter into the cerebellar cortex is likely to cause the specific transduction of neuronal cells, such as Purkinje cells (PCs) and interneurons, but not Bergmann glia (BG). However, we found BG-predominant transduction without PC transduction along a traumatic needle tract for viral injection. The enhancement of neuroinflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Since the identification of the L7-4 sequence as an effective Purkinje cell-specific promoter suitable for viral vectors, the promoter has been widely used to date. 28 , 29 , 30 , 31 Nevertheless, we and others have noted a diffuse transduction in non-Purkinje cells in the molecular and granule cell layers. In addition, the L7 splice variants that use different ATG in exon 1 as a translation initiation codon (forms B and C) prompted us to narrow down the L7 further to a shorter promoter with a more restricted leakage to other cell types.…”
Section: Resultsmentioning
confidence: 44%
See 1 more Smart Citation
“…Since the identification of the L7-4 sequence as an effective Purkinje cell-specific promoter suitable for viral vectors, the promoter has been widely used to date. 28 , 29 , 30 , 31 Nevertheless, we and others have noted a diffuse transduction in non-Purkinje cells in the molecular and granule cell layers. In addition, the L7 splice variants that use different ATG in exon 1 as a translation initiation codon (forms B and C) prompted us to narrow down the L7 further to a shorter promoter with a more restricted leakage to other cell types.…”
Section: Resultsmentioning
confidence: 44%
“…In a yet unpublished previous study using lentiviral vectors, we found that a 1-kb fragment of the L7 promoter exhibited strikingly greater promoter strength than the original 3-kb L7 promoter (US Patent 8912315 B2), 27 although the experimental procedure to obtain the 1-kb fragment and the sequence have not yet been published. Subsequent utilization of the compact 1-kb promoter by several groups, including ours, 28 , 29 , 30 , 31 revealed overall maintenance of the Purkinje cell selectivity, but with some diffuse activity in off-target cells.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of lactate shuttle systems extends to other types of neuronal cells, such as the oligodendrocyte–axon lactate shuttle (Baltan, 2015 ) and the Bergmann glia (BG) Purkinje cell (PC) lactate shuttle (Sawada et al, 2016 ). Lactate shuttles extend beyond the brain—they are of particular interest in cancer research (Pizzuto et al, 2012 ).…”
Section: The Brain In Crisismentioning
confidence: 99%
“…RT‐qPCR and Western blot assay analyses indicated that in comparison to the cells in Noggin group, the cells in Noggin + Y‐27632 group showed an significantly elevated expression of NES, Nestin, and GFAP. NSE, a glycolytic isoenzyme, is found in mature neurons and cells of neuronal origin . Binding of overexpressed Noggin to NSE promoter (NSE‐Noggin) has been shown to enhance neurological functions like learning and memory, which are associated with BMP signaling components in the hippocampus .…”
Section: Discussionmentioning
confidence: 99%
“…NSE, a glycolytic isoenzyme, is found in mature neurons and cells of neuronal origin. 27 Binding of overexpressed Noggin to NSE promoter (NSE-Noggin) has been shown to enhance neurological functions like learning and memory, which are associated with BMP signaling components in the hippocampus. 28 Moreover, in agreement to our results, a previous study has also proved that bone marrow derived mesenchymal stem cells transfected with Noggin gene can differentiate into neuron-like cells in vitro, and such activity is associated with the expression of NSE, neurofilament 200, neuronal nuclei, and GFAP.…”
Section: Discussionmentioning
confidence: 99%